Building Institutional Competitiveness through Training, Career Development and Motivation - Widana, I Gede; Heryanda, Komang Krisna; Telagawathi, Ni Luh Wayan Sayang (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyze the influence of training, career development, and work motivation on the performance of administrative staff at Ganesha University of Education. The research employs a quantitative method with an associative approach. Data were collected through questionnaires distributed to 121 administrative employees selected using a saturated sampling technique. The data were analyzed using multiple linear regression with SPSS. The results show that training, career development, and work motivation have a significant positive effect on employee performance. These findings emphasize the importance of human capital investment in improving institutional performance. The study recommends that university management enhance the effectiveness of training programs, clarify career development paths, and implement more effective reward systems to foster employee motivation and improve performance outcomes.